RELATIONSHIP BETWEEN COMPRESSIVE STRENGTH AND FLEXURAL STRENGTH IN REACTIVE POWDER CONCRETE - Girsang, Pije Saputra; Naibaho, Pio Ranap Tua; Bangun, Sempurna (Universitas Trisakti, 2023)
Reactive powdered concrete is a new type of concrete which has ultra high compressive strength. The constituent components are very fine powders which have a high silica content. This aims to improve the reaction that occurs in concrete and increase the homogeneity of the concrete. Reactive powder concrete consists of cement, silica fume, quartz with a maximum diameter of 300 μm, superplasticizer and steel fiber to increase ductility. Reactive powder concrete which has high compressive strength and high ductility has the potential to replace steel materials in construction work. Has a very big opportunity for construction materials in Indonesia considering the availability of the materials needed, especially quartz. This research is the first step towards the possibility of developing reactive powdered concrete in Indonesia, which is based on previous research. Experiments were carried out to obtain a reactive powdered concrete mixture with local materials. This experimental behavior serves to connect the compressive strength and bending with the formula 0.62fc '. The results showed that the compressive strength was 32.85 MPa and the flexural strength 3.25 MPa and the compressive strength produced by the reactive powder concrete was of medium quality concrete, this was due to differences in the composition and characteristics of the superplasticizer, silica fume, cement, or sika fiber used